Regulation of cardiac hypertrophy and remodeling through the dual-specificity MAPK phosphatases (DUSPs) - Liu, Ruijie (J Mol Cell Cardiol, 2016)
Mitogen-activated protein kinases (MAPKs) play a critical role in regulating cardiac hypertrophy and remodeling in response to increased workload or pathological insults. The spatiotemporal activities and inactivation of MAPKs are tightly controlled by a family of dual-specificity MAPK phosphatases (DUSPs). Over the past 2 decades, we and others have determined the critical role for selected DUSP family members in controlling MAPK activity in the heart and the ensuing effects on ventricular growth and remodeling. More specifically, studies from mice deficient for individual Dusp genes as well as heart-specific inducible transgene-mediated overexpression have implicated select DUSPs as essential signaling effectors in the heart that function by dynamically regulating the level, subcellular and temporal activities of the extracellular signal-regulated kinases (ERKs), c-Jun N-terminal kinases (JNKs) and p38 MAPKs. This review summarizes recent literature on the physiological and pathological roles of MAPK-specific DUSPs in regulating MAPK signaling in the heart and the effect on cardiac growth and remodeling.